CT Scan Evaluation of the Maxillary Sinus Pathologies: Intrinsic and Extrinsic - Bhaskar K Patle; Hemant Umarji (Wolters Kluwer Medknow Publications, 2010)
The pathologies affecting the maxillary sinus and related structures namely cyst, tumors and infections become difficult to diagnose/localize due to the existing complex arrangement of various bone forming maxillofacial complex. CT has become an indispensable tool in the diagnosis of maxillary sinus pathologies. However, being a fairly recent technology, we (oral and maxillofacial radiologist) have not gained expertise in the interpretation of this fascinating imaging modality. Considering all these factors, one is compelled to accept the fact that not only is CT. a valuable tool in our field of maxillofacial radiology but it has become a vital time saving, safe and painless investigation in the evaluation of maxillofacial complex. A total number of 25 patients of maxillary sinus pathologies (intrinsic and extrinsic) were included in the study and were subjected to detailed case history, clinical examination, conventional radiography and CT scan. The results obtained in our study are discussed and compared with other similar studies.